Long-term Outcomes and Factors Predicting Outcome of IPAA When Used Intentionally for Well-Defined Crohn's Disease. Issue 5 (1st March 2023) - Aviran, Eyal; Assaf, Dan; Zaghiyan, Karen; Fleshner, Phillip
Abstract : BACKGROUND: Crohn's disease is considered a contraindication for IPAA. In our prior study, when IPAA was used intentionally for well-defined Crohn's disease, we found a high incidence of recurrent disease with a low incidence of pouch failure. OBJECTIVE: This study aimed to replicate these findings in a larger cohort over a longer period. DESIGN: Retrospective review of a prospective IBD registry. SETTINGS: Large IBD referral center. PATIENTS: Patients with preoperative colorectal Crohn's disease requiring surgery were included in the study. INTERVENTION: IPAA. MAIN OUTCOME MEASURES: Long-term Crohn's disease recurrence, pouch failure, and pouch function. RESULTS: Forty-six patients were identified. Crohn's disease was diagnosed on the basis of perianal disease (n = 18; 39%), small-bowel disease (n = 16; 35%), noncaseating granuloma (n = 10; 22%), and discontinuous inflammation (colorectal skip lesions) (n = 11; 24%). After a median follow-up of 93 (7–291) months, 22 patients (48%) developed recurrent Crohn's disease based on afferent limb disease (n = 14; 30%) or pouch fistulizing disease (n = 8; 18%). Only 4 patients (9%) developed pouch failure. No clinical factor was associated with Crohn's disease recurrence. Young age at the time of surgery and short duration of disease before IPAA were associated with pouch fistula recurrence ( p = 0.003 and p = 0.03, respectively). Most patients (86%) reported excellent continence, with no urgency (67%) and median stool frequency of 6 (range, 3–9) per day. LIMITATION: Retrospective nature and relatively small sample size. CONCLUSION: This largest reported series examining the intentional use of IPAA in Crohn's disease showed a high (48%) incidence of postoperative Crohn's disease with a low (9%) incidence of pouch failure. Young age and short disease course before surgery were risk factors for poor outcomes. Highly motivated patients with colorectal Crohn's disease may consider IPAA and avoid a definitive ileostomy. See Video Abstract at http://links.lww.com/DCR/C171 . RESULTADOS A LARGO PLAZO Y FACTORES PREDICTORES DE RESULTADOS DE LA ANASTOMOSIS ILEOANAL CON RESERVORIO CUANDO SE USA INTENCIONALMENTE PARA LA ENFERMEDAD DE CROHN BIEN DEFINIDA : ANTECEDENTES: La enfermedad de Crohn (EC) se considera una contraindicación para la anastomosis ileoanal con reservorio (IPAA). Nuestro estudio previo de IPAA cuando fue usada intencionalmente para EC bien definida mostró una alta incidencia de enfermedad recurrente con una baja incidencia de falla del reservorio. OBJETIVO: Replicar estos hallazgos en una cohorte más grande durante un período más largo. DISEÑO: Revisión retrospectiva de una base de datos prospectiva de enfermedad inflamatoria intestinal. ESCENARIO: Un centro grande de referencia de EII. PACIENTES: EC colorrectal preoperatoria con necesidad de tratamiento quirúrgico. INTERVENCIÓN: Anastomosis ileoanal con reservorio. RESULTADOS PRINCIPALES: Recurrencia de EC a largo plazo, falla del reservorio y función del reservorio. RESULTADOS: Cuarenta y seis pacientes fueron identificados. El diagnóstico de EC se basó en enfermedad perianal (n = 18; 39%), enfermedad del intestino delgado (n = 16; 35%), granuloma no caseificante (n = 10; 22%) e inflamación discontinua (lesiones salteadas colorrectales) (n = 11; 24%). Después de una mediana de seguimiento de 93 (7-291) meses, 22 (48 %) pacientes desarrollaron EC recurrente debido a enfermedad del asa aferente (n = 14; 30%) o enfermedad fistulizante del reservorio (n = 8; 18%). Solo 4 (9%) pacientes desarrollaron falla del reservorio. Ningún factor clínico se asoció con la recurrencia de EC. La edad joven en el momento de la cirugía y la corta duración de la enfermedad antes de IPAA se asociaron con la recurrencia de la fístula del reservorio ( p = 0.003 y p = 0.03, respectivamente). El recuento de plaquetas preoperatorio más alto fue la única característica clínica significativamente asociada con el fracaso del reservorio ( p = 0.02). La mayoría de los pacientes (86%) reportaron una continencia excelente, sin urgencia (67%) y una mediana de frecuencia evacuatoria de 6 (rango, 3-9) por día. LIMITACIONES: Naturaleza retrospectiva y tamaño de muestra relativamente pequeño. CONCLUSIÓN: Esta serie, la más grande reportada que examina el uso intencional de IPAA en la EC mostró una incidencia alta (48Rectal Cancer: Clinical and Molecular Predictors of a Complete Response to Total Neoadjuvant Therapy%) de EC posoperatoria con una incidencia baja (9%) de falla del reservorio. La edad joven y el curso corto de la enfermedad antes de la cirugía fueron factores de riesgo para pobres resultados. Pacientes altamente motivados con EC colorrectal pueden considerar una IPAA y evitar una ileostomía permanente. Consulte Video Resumen en http://links.lww.com/DCR/C171 . (Traducción—Dr. Jorge Silva Velazco ) Video Abstract: